Pengaruh Pengungkapan Sustainability Report Terhadap Kinerja Keuangan Perusahaan - Yudi Partama Putra; Tekad Adi Subroto (UNIVED Press, 2022)
This study aimed to examine the effect between sustainability report disclosure to financial performance with proksi Return on Assets (ROA), Return on Equity (ROE) and Current Ratio (CR). The Global Reporting Initiative (GRI) G4 was a guidelines (91 item) and GRI Standards (77 item) in measuring the sustainability report disclosure. It was calculated by Sustainability Report Disclosure Index (SRDI). Population of this study was the all company except non-financial companies that listed in Indonesia Stock Exchange period 2016-2018. The technique used in this study was purposive sampling with 25 samples of the companies were selected which in the period of three years, so there were 75 samples data. The data analysis methods of this research was panel data regression analysis by using Eviews 9. The result of this research shows that sustainability report disclosure have significant effect toward financial performance with proksi ROA. Sustainability report disclosure have a significant effect toward financial performance with proksi ROE. Sustainability report disclosure have no effect toward financial performance with proksi (CR).